PENGUATAN KAPASITAS KELOMPOK NELAYAN MELALUI PELATIHAN KELEMBAGAAN DI DESA PADANG SEURAHET KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Arfriani Maifizar; Nurhaslita Sari (Jurnal Pengabdian Agro and Marine Industry, 2022)
Research-based service activities in the form of and assistance in terms of strengthening the institutional capacity of fisherman groups. The participants involved in this activity were 15 people from local village officials, fisherman group administrators and BUMDES administrators in the village. The methods used in this training include: lectures, questions and answers, and forum discussion groups (FGD). This service activity in particular has led to the achievement of several objectives including: in the cognitive aspect, there has been an increase in the understanding of the participants regarding the operational steps for strengthening the institutional capacity of fishermen groups, such as in terms of administrative activities, community empowerment activities, designing collaborative activities, utilizing aid from the government, and the establishment of an organizational structure along with the roles and functions within the institutional structure. In the practical aspect, it appears that there is a strong desire and awareness for fishing groups to increase the institutional capacity of fishing groups through various steps taken from what was conveyed during the service activity